External debt and Economic Growth of Nepal - Adhikari, Saurav (The Lumbini Journal of Business and Economics, 2023)
This paper examines the effect of external debt and economic growth of Nepal over the period of 1978-2020.The external debt of Nepal has been significantly increasing during the study period. The objective of this study is to examine the effect of external debt on economic growth of Nepal by ARDL model. Descriptive and analytical research design has been used by using secondary data. The finding of the study concluded Balance of payment has positively significantly impact on the growth in GDP respectively at 5% level of significance. Total external debt and Total reserves haspositive insignificant effect economic growth respectively. The findings of this study revealed that increase in balance of payment increases the growth of the economy of Nepal. The optimal use of external debt should be for national growth in order to expand the size of the market, improve the skill and productivity of workers, decrease geographic fragmentation, and boost the profitability of private investment to increase the GDP of the country.